2009
DOI: 10.1152/ajprenal.90488.2008
|View full text |Cite
|
Sign up to set email alerts
|

Localization of ACE2 in the renal vasculature: amplification by angiotensin II type 1 receptor blockade using telmisartan

Abstract: converting enzyme (ACE)2 is a carboxypeptidase that degrades angiotensin II and other peptides. In the kidney, ACE2 localization within the glomerulus and tubules is cell specific. This study was aimed to investigate the localization of ACE2 within the renal vasculature. We also studied the effect of the administration of a specific angiotensin II type 1 receptor blocker, telmisartan, on ACE2 expression in the renal vasculature. ACE2 and ACE were localized in renal arterioles using confocal microscopy and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
186
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(197 citation statements)
references
References 38 publications
9
186
1
1
Order By: Relevance
“…In the present study, 5 ⁄6 Nx mice treated with losartan showed no decrease in kidney ACE2 expression. Similar to our data, treatment of adult Lewis rats with losartan increased kidney cortex ACE2 activity (6), while in C57BLKS/J mice the AT 1 receptor antagonist telmisartan increased ACE2 protein expression in the renal vasculature (31).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, 5 ⁄6 Nx mice treated with losartan showed no decrease in kidney ACE2 expression. Similar to our data, treatment of adult Lewis rats with losartan increased kidney cortex ACE2 activity (6), while in C57BLKS/J mice the AT 1 receptor antagonist telmisartan increased ACE2 protein expression in the renal vasculature (31).…”
Section: Discussionsupporting
confidence: 90%
“…In mice, expression of ACE2 in the tunica media of renal arterioles contrasts with the expression of ACE in the vascular endothelium of these arterioles (129). As first shown by us in the heart (68) and the aorta (65, 66), administration of an ANG II receptor antagonist leads to an increase kidney arteriole ACE2 gene expression (129). In keeping with previous studies (28), renal expression of ACE2 was reduced by kidney disease and subtotal nephrectomy (78).…”
supporting
confidence: 81%
“…ACE2 within the kidneys colocalizes with ACE in proximal and distal tubules and in podocytes within the glomerulus (87,133,156). In mice, expression of ACE2 in the tunica media of renal arterioles contrasts with the expression of ACE in the vascular endothelium of these arterioles (129). As first shown by us in the heart (68) and the aorta (65, 66), administration of an ANG II receptor antagonist leads to an increase kidney arteriole ACE2 gene expression (129).…”
mentioning
confidence: 92%
“…In previous studies (43,47) it was found that ACE2 is increased in kidney cortex but decreased by immunostaining in glomeruli from young db/db mice (8 wk of age). In other models of diabetic kidney disease (Akita and in STZ-treated mice) kidney ACE2 protein or activity were also reported to be elevated in kidney cortex (33,35,40,43). In the present study, we measured ACE2 activity in both glomerular and tubular kidney isolates from older db/db mice (32 wk of age) and found that tubular ACE2 activity was increased compared with db/m controls.…”
Section: Discussionsupporting
confidence: 52%